The Gut Microbiota Reduces Colonization of the Mesenteric Lymph Nodes and IL-12-Independent IFN-γ Production During Salmonella Infection - Fernández-Santoscoy, María; Wenzel, Ulf A.; Yrlid, Ulf; Cardell, Susanna; Bäckhed, Fredrik; Wick, Mary Jo (Frontiers in Cellular and Infection Microbiology, 2015)
The intestinal commensal microbiota is essential for many host physiological processes, but its impact on infectious diseases is poorly understood. Here we investigate the influence of the gut microbiota during oral Salmonella infection. We report a higher bacterial burden in mesenteric lymph nodes (MLN) of intragastrically infected germ-free (GF) mice compared to conventionally-raised (CONV-R) animals, despite similar inflammatory phagocyte recruitment. Salmonella penetration into the lamina propria of the small intestine and splenic bacterial burden were not altered in the absence of the microbiota. Intragastrically infected GF mice also displayed a higher frequency of IFN-γ-producing NK, NKT, CD4+ and CD8+ T cells in the MLN despite IL-12 levels similar to infected CONV-R mice. However, infecting mice intraperitoneally abrogated the difference in MLN bacterial load and IFN-γ-producing cells observed in intragastrically-infected animals. Moreover, mice treated with antibiotics (ABX) and intragastrically infected with Salmonella had a greater bacterial burden and frequency of IFN-γ-producing cells in the MLN. In ABX mice the number of Salmonella correlated with the frequency of IFN-γ-producing lymphocytes in the MLN, while no such correlation was observed in the MLN of infected GF mice. Overall, the data show that the lack of the microbiota influences pathogen colonization of the MLN, and the increased IFN-γ in the MLN of infected GF mice is not only due to the absence of commensals at the time of infection but the lack of immune signals provided by the microbiota from birth.